THE ROLE OF SMALL RNAS IN CONTROLLING EXPRESSION OF GENES INVOLVED IN THE IMPLEMENTATION OF VIBRIO CHOLERAE PATHOGENICITY - R. V. Pisanov; A. S. Vodop’yanov; D. I. Simakova (Проблемы особо опасных инфекций, 2017)
Currently, bacterial small RNAs with regulatory functions are characterized as a heterogeneous claster of highly structured single-stranded RNAs which usually would not be translated into proteins. A large group of small RNAs consists of small regulatory RNAs functioning through the mechanism of complementary interaction between small regulatory RNA bases and bacterial messenger RNAs (mRNA). The review provides the description of direct participation of small RNA mechanisms in realization of pathogenic properties, biofilm formation and virulence regulation in V. cholerae strains. In particular, the Hfq-dependent small RNAs that control the expression of genes responsible for virulence and biofilm formation of V. choleraе, and the impact of small RNA on the secretion system of VI type are presented. We also characterized the small RNAs–controlled process of V. cholerae vesicles formation, which have a great significance for colonization ability of cholera vibrios. In addition, such method of regulation at RNA level as “riboswitches”, (RNA switches) is described.